Estimation of steady-state stability limit of the electric power system current regime to improve reliability of power supply - Yuneeva, Natalia; Danko, Alexey; Izvolenskiy, Igor (My University, 2013)
The research resulted in the technique of monitoring the current stock of static stability in the cross section of the EPS based on the criterion of the regime of using synchronized measurements phase of voltage in electrical network remote sites with visual trajectory weighting.
Keywords: power system; steady-state stability; phase synchronized measurement; електроенергетична система; статична стійкість; синхронизоване вимірювання фаз; электроэнергетическая система; статическая устойчивость; синхронизированное измерение фаз; кафедра електропостачання і енергоменеджменту